On interpretation - Michał Januszkiewicz (Przestrzenie Teorii)
The article entitled “On interpretation” is an attempt to formulate a viewpoint on the issue of textual interpretation. It presents different ideas related to interpretation, including especially those that are concerned with a text’s meaning and with the way in which it is interpreted by the reader. The author proposes another interpretation method which he calls transactional. The primary concern is how to possibly justify the fundamental character of interpretation and interpretative activity while at the same time preserving and respecting the relative autonomy of an interpreted text.